Hydrogels and Nanogels (IntechOpen, 2024)
This book provides an overview of hydrogels and nanogels, including their manufacturing techniques, physicochemical and mechanical properties, and applications in medicine, as well as bioengineering strategies and their impacts on the functions of carrier systems. It explores the fundamentals of the synthesis, synthetic chemistry, and development of hydrogels and nanogels. It discusses the fabrication of stimuli-responsive hydrogels and nanogels and biomaterial requirements, as well as reviews the various classifications of hydrogels and nanogels and their self-assembly and gelation mechanisms. The book also highlights the mechanisms of drug encapsulation and release from hydrogels and nanogels and their biocompatibility with physiological membranes. Furthermore, it provides information on how to modify or engineer the surface of biomimetic systems for targeting purposes and the materials to be used to realize this objective. The book discusses factors to consider for the clinical translation of hydrogels and nanogels. Finally, it discusses the biomedical applications of hydrogels and nanogels, including in drug delivery, wound healing, and neurological and ophthalmic diseases.